Bakteri Bacillus sp. Berpotensi Probiotik dalam Saluran Pencernaan Ikan Bawal Bintang Trachinotus blochii - Aminatul Zahra; Sri Novalina Amrizal (Intek Akuakultur, 2022)
Isolation of Bacillus sp. the potential for probiotics in the digestive tract of Silver Pompano has never been carried out. Therefore it is necessary to research the isolation and selection of Bacillus sp. potential probiotics in the digestive tract of Silver Pompano to increase growth and feed efficiency. Bacteria were isolated from the digestive tract of Silver Pompano to ensure that the isolates obtained were from Bacillus sp. then gram staining and spore staining were performed on the isolates obtained. After that, a Proteolytic, Lipolytic, Amylolytic Activity test was carried out, then a Resistance Test to Stomach Acid and Bile Salts, as well as a bacterial growth test for 24 hours. There are six isolates of Bacillus sp., which have the potential for probiotics in Silver Pompano's digestive tract, which has the ability of proteolytic, lipolytic, and amylolytic enzyme activity and is resistant to acid and alkaline conditions.